Enzymatic Formation of Xanthurenic Acid 8-Methyl Ether, an Endogenous Carcinogen, in Animal Tissues - SUZUKI, MAKIKO; WATANABE, MITSUO; TABARA, MASAYOSHI; IINUMA, FUMIO (Chemical & pharmaceutical bulletin, 1984)
An enzyme activity forming xanthurenic acid 8-methyl ether, a carcinogenic tryptophan metabolite, was found in the organs of various animals by using a new method of analysis. After incubation of a 105000g supernatant of the tissues with xanthurenic acid and S-adenosylmethionine at pH 10.0, the xanthurenic acid 8-methyl ether was separated by high-performance liquid chromatography on a LiChrosorb RP-18 column and determined fluorometrically. Potent enzyme activity was found in the liver and kidney of pig and wild boar, and in bovine liver. Low activity was found in the liver and kidney of sheep, deer, and monkey. Our data suggest that the ether may be formed from xanthurenic acid by this enzyme, because the enzyme activity was high in porcine liver, and pigs excrete xanthurenic acid 8-methyl ether in the urine.